PENGGUNAAN MEDIA WORDWALL UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS III-C SD NEGERI 25 PALU PADA MATA PELAJARAN IPAS - Annastasya Bungin; Rizal; Rommy AR (STKIP Subang, 2025)
This Classroom Action Research (CAR) aimed to improve student activeness through the use of Wordwall media. The study involved 21 Grade III-C students at SD Negeri 25 Palu, consisting of 11 girls and 10 boys. Data were collected using observation techniques to measure student activeness. The research was conducted from the pre-action stage to Cycle II. The results showed a significant increase in student activeness during IPAS lessons. In the pre-action stage, the average activeness score was 48%, categorized as Low. In Cycle I, it rose to 69%, categorized as Medium. By Cycle II, the score increased further to 83%, categorized as High. These findings indicate that Wordwall media effectively enhanced student engagement and participation in the classroom. Therefore, it can be concluded that using Wordwall as a learning tool successfully improved the activeness of Grade III-C students at SD Negeri 25 Palu in the IPAS subject.